Transcription factor 21 accelerates vascular calcification in mice by activating the IL-6/STAT3 signaling pathway and the interplay between VSMCs and ECs - Zhao Xiao-kang; Zhu Meng-meng; Wang Sheng-nan; Zhang Ting-ting; Wei Xiao-ning; Wang Cheng-yi; Zheng Juan; Zhu Wen-ya; Jiang Mei-xiu; Xu Suo-wen; Yang Xiao-xiao; Duan Ya-jun; et al. (Acta Pharmacologica Sinica; Vol 44, No 8 (August 2023): Acta Pharmacologica Sinica, 2023)
Vascular calcification is caused by the deposition of calcium salts in the intimal or tunica media layer of the aorta, which increases the risk of cardiovascular events and all-cause mortality. However, the mechanisms underlying vascular calcification are not fully clarified. Recently it has been shown that transcription factor 21 (TCF21) is highly expressed in human and mouse atherosclerotic plaques. In this study we investigated the role of TCF21 in vascular calcification and the underlying mechanisms. In carotid artery atherosclerotic plaques collected from 6 patients, we found that TCF21 expression was upregulated in calcific areas. We further demonstrated TCF21 expression was increased in an in vitro vascular smooth muscle cell (VSMC) osteogenesis model. TCF21 overexpression promoted osteogenic differentiation of VSMC, whereas TCF21 knockdown in VSMC attenuated the calcification. Similar results were observed in ex vivo mouse thoracic aorta rings. Previous reports showed that TCF21 bound to myocardin (MYOCD) to inhibit the transcriptional activity of serum response factor (SRF)-MYOCD complex. We found that SRF overexpression significantly attenuated TCF21-induced VSMC and aortic ring calcification. Overexpression of SRF, but not MYOCD, reversed TCF21- inhibited expression of contractile genes SMA and SM22. More importantly, under high inorganic phosphate (3 mM) condition, SRF overexpression reduced TCF21-induced expression of calcification-related genes (BMP2 and RUNX2) as well as vascular calcification. Moreover, TCF21 overexpression enhanced IL-6 expression and downstream STAT3 activation to facilitate vascular calcification. Both LPS and STAT3 could induce TCF21 expression, suggesting that the inflammation and TCF21 might form a positive feedback loop to amplify the activation of IL-6/STAT3 signaling pathway. On the other hand, TCF21 induced production of inflammatory cytokines IL-1β and IL-6 in endothelial cells (ECs) to promote VSMC osteogenesis. In EC-specific TCF21 knockout (TCF21ECKO) mice, VD3 and nicotine-induced vascular calcification was significantly reduced. Our results suggest that TCF21 aggravates vascular calcification by activating IL-6/STAT3 signaling and interplay between VSMC and EC, which provides new insights into the pathogenesis of vascular calcification.